Association between antibiotics and dementia risk: A retrospective cohort study - Kim, Minseo; Park, Sun Jae; Choi, Seulggie; Chang, Jooyoung; Kim, Sung Min; Jeong, Seogsong; Park, Young Jun; Lee, Gyeongsil; Son, Joung Sik; Ahn, Joseph C.; Park, Sang Min (Frontiers in Pharmacology, 2022)
BACKGROUND The possible relation between antibiotic exposure and the alteration of gut microbiota, which may affect dementia risk, has been revealed. However, the association between antibiotics and dementia incidence has rarely been studied. We aimed to determine the association between antibiotic exposure and the risk of dementia. METHODS This population-based retrospective cohort study used data from the National Health Insurance Service-Health Screening Cohort (NHIS-HEALS) in South Korea. Exposure was the cumulative days of antibiotic prescription from 2002 to 2005. Newly diagnosed overall dementia, Alzheimer’s disease (AD), and vascular dementia (VD) were identified based on diagnostic codes and prescriptions for dementia-related drugs. The follow-up investigation was carried out from 1 January 2006 to 31 December 2013. The Cox proportional hazards regression was used to assess the association between cumulative antibiotic prescription days and dementia incidence. RESULTS A total of 313,161 participants were analyzed in this study. Compared to antibiotics non-users, participants who used antibiotics for 91 or more days had an increased risk of overall dementia (adjusted hazard ratio [aHR], 1.44; 95% confidence interval [CI], 1.19 to 1.74), AD (aHR, 1.46; 95% CI, 1.17 to 1.81), and VD (aHR, 1.38; 95% CI, 0.83 to 2.30). Those who used five or more antibiotic classes had higher risks of overall dementia (aHR, 1.28; 95% CI, 1.00 to 1.66) and AD (aHR, 1.34; 95% CI, 1.00 to 1.78) than antibiotics non-users. CONCLUSION Antibiotic exposure was associated with an elevated risk of dementia in a cumulative duration-dependent manner among adult participants. These results suggest the need for antibiotic stewardship and limiting the long-term prescription of antibiotics.